BURN ANEMIA: CAUSES AND DIFFICULTIES OF TREATMENT AT THE PRESENT STAGE - V. S. Borisov; S. V. Smirnov (Неотложная медицинская помощь, 2016)
ABSTRACT. The article presents the results of experiments and clinical research of the last decades in the sphere of study of the anemia development pathogenesis in burn patients. Burn anemia was proven to have multifactor genesis and combine both manifestations of acute anemia, hemolysis (primary, seconary), mechanical blood loss, hemorrhagic syndrome and symptoms of chronic autoimmune anemia. It has been shown how the principles of transfusion therapy in burn patients have been changing during the last 30 to 40 years, and what kind of contradictions exist at the present stage in defining strategies for treatment of patients with burn anemia. The article presents the results of our own observations, materials of foreign multi-center studies, analysis of the most promising and up-todate recommendations to prevent or ameliorate the adverse effects of anemia on the condition of a burn patient.